2020
DOI: 10.1021/acs.jmedchem.9b01442
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of 2,5-Substituted Benzoic Acid Dual Inhibitors of the Anti-apoptotic Mcl-1 and Bfl-1 Proteins

Abstract: Anti-apoptotic Bcl-2 family proteins are overexpressed in a wide spectrum of cancers and have become well validated therapeutic targets. Cancer cells display survival dependence on individual or subsets of anti-apoptotic proteins that could be effectively targeted by multimodal inhibitors. We designed a 2,5-substituted benzoic acid scaffold that displayed equipotent binding to Mcl-1 and Bfl-1. Structure-based design was guided by several solved cocrystal structures with Mcl-1, leading to the development of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…These include S64315/MIK665 (71), AZD-5991 (72), PRT1419 (73), and AMG-176 (74), among others, which are currently being explored in clinical trials (NCT02992483, NCT04629443, NCT03013998, NCT02675452, NCT04178902, NCT04543305, and others), mostly in hematologic malignancies. Other compounds that inhibit or degrade MCL1 have also demonstrated activity in preclinical models (75)(76)(77)(78). Given that MCL1 is a shortlived protein (79), indirect targeting by CDK9 inhibitors, such as alvocidib, AZD4573 (NCT03263637), or voruciclib (NCT03547115), or protein selective degradation approaches (75) have emerged as alternative strategies (80).…”
Section: Reviewmentioning
confidence: 99%
“…These include S64315/MIK665 (71), AZD-5991 (72), PRT1419 (73), and AMG-176 (74), among others, which are currently being explored in clinical trials (NCT02992483, NCT04629443, NCT03013998, NCT02675452, NCT04178902, NCT04543305, and others), mostly in hematologic malignancies. Other compounds that inhibit or degrade MCL1 have also demonstrated activity in preclinical models (75)(76)(77)(78). Given that MCL1 is a shortlived protein (79), indirect targeting by CDK9 inhibitors, such as alvocidib, AZD4573 (NCT03263637), or voruciclib (NCT03547115), or protein selective degradation approaches (75) have emerged as alternative strategies (80).…”
Section: Reviewmentioning
confidence: 99%
“…A conserved BimBH3 peptide consisting of 14 residues was modified by inserting two cyclization constraints to generate bicyclic helical peptides, which were potent, cell-permeable, dual inhibitors of Bcl-2A1/Bfl-1 and Mcl-1 with high selectivity over other Bcl-2 proteins [ 121 ]. Another study reported the design of dual Mcl-1/Bfl-1 inhibitors based on benzoic acid scaffolds, where a compound 24 binds to both Mcl-1 and Bfl-1 with inhibitor constant Ki of 100 nmol/L and exhibits great selectivity over Bcl-2/Bcl-xl [ 122 ]. The natural compound marinopyrrole A has been shown to degrade Mcl-1 protein and thereby induce apoptosis in Mcl-1-dependent cancer cells [ 123 ].…”
Section: Therapeutic Targeting Of Mcl-1mentioning
confidence: 99%
“…An FP competition assay was used to evaluate the inhibitory activities of the compounds against Mcl-1, 75 Bcl-2, 68 and Bfl-1. 76 Different concentrations of compounds were prepared by serial dilution in assay buffer (Mcl-1: 20 mM Tris, 150 mM NaCl, 3 mM DTT, pH = 7.5; Bfl-1 and Bcl-2: 55 mM Hepes, 274 mM NaCl, 1.48 mM Na 2 HPO 4 , pH = 7.0). FITC-Bak-BH3 was chosen as a probe for Mcl-1 (10 nM final).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%